Audit Syariah Indonesia: Tinjauan atas Peluang dan Tantangan Perkembangan - Fani Rahmadhani; Nuraisyah Arif; Masyhuri (Journal of Islamic Economic Studies, 2025)
Sharia audit in Indonesia has great potential along with the rapid growth of the Islamic financial industry. This study aims to explore the opportunities and challenges faced in the development of sharia audit in Indonesia. The method used is qualitative analysis by collecting data from various literature sources and case studies related to sharia audit practices. The results of the study indicate that although there are significant opportunities, such as increasing public awareness of the importance of sharia compliance and regulatory support from the government, challenges remain. These challenges include the lack of comprehensive sharia audit standards, the limited number of qualified sharia auditors, and the issue of independence of the Sharia Supervisory Board (DPS). This study concludes that in order to maximize the potential of sharia audit, there is a need for strengthening regulations, improving the quality of human resources, and developing a better audit framework. Thus, sharia audit can contribute effectively to maintaining the integrity and accountability of Islamic financial institutions in Indonesia.